2016
DOI: 10.2147/prbm.s112129
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, perceived stigma, and coping among caregivers of patients with schizophrenia

Abstract: Nowadays, family members are gradually taking on the role of full-time caregivers for patients suffering from schizophrenia. The increasing burden and tasks of caretaking can cause them psychological distress such as depression or anxiety. The aim of this study was to measure the correlation between perceived stigma and coping, and psychological distress as well as determine the predictors of psychological distress among the caregivers. Results showed that 31.5% of the caregivers experienced psychological dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
69
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 46 publications
9
69
2
3
Order By: Relevance
“…The strategies used by individuals to cope with disease and the care burden have a significant effect on the quality of care provided for the patient . The care commitment strategy exhibited by the caregivers of dialysis patients in this study represents an active and sustainable strategy that results from the caregivers' beliefs and cultural and religious values.…”
Section: Discussionmentioning
confidence: 90%
“…The strategies used by individuals to cope with disease and the care burden have a significant effect on the quality of care provided for the patient . The care commitment strategy exhibited by the caregivers of dialysis patients in this study represents an active and sustainable strategy that results from the caregivers' beliefs and cultural and religious values.…”
Section: Discussionmentioning
confidence: 90%
“…Delusion‐associated consequences have substantial, multidimensional impacts on patients, which in turn affect them at work or home (Coid et al., ). Patients’ violent behavior associated with delusion can become more severe during the course of the illness, increasing the caretaking burden of family caregivers and gradually damaging their mental well‐being (Lam, Ng, & Tori, ), and psychological distress (Ong, Ibrahim, & Wahab, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both associative and affiliate stigma lead to destructive effects on caregivers; however, the consequences of caregiver stigma intensify when the caregivers endorse or accept the negative public attitudes they perceive, that is, affiliate stigma is more serious than associative stigma (Girma et al., ). Research on caregivers of PWMI reported that affiliate stigma may compromise the health condition of the patient by creating care burden, enhancing psychological distress and decreasing the QoL (Ong, Ibrahim, & Wahab, ; Wu & Chen, ). Consequently, the help‐seeking behaviour of the patient is suppressed, thereby exacerbating the severity of the disease (Fernando, Deane, & McLeod, ).…”
Section: Introductionmentioning
confidence: 99%